Ellipsis is a basal phenomenon and aesthetic function (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Ellipsis is a linguistic phenomenon which was greatly cared for by traditional Arab linguistic lesson by leading linguists of both grammarians and rhetoricians, but this care remained signal locked to the ellipsis locations, to know its reasons and its rhetorical purpose, far away from diving into its real aesthetic dimensions.This research will submit ellipsis as an aesthetic element of language aesthetics, and an indicator on its vitality which exceeds rules limits, and revels what are there between lines of meanings and secrets, as it will reveal that ellipsis reversion absolutely for reasons, like : disregard, or overuse, or denominator and saying significance on the omitted text and other reasons which came from grammarians, and briefing or wishing mercy, or exclamation  and others of the guided indications of what came from the rhetoricians, it has restriction of language moving towards building new contextual relations full of beauty and new implied meanings.